MATEMATIKA DALAM SENI ARABESQUE: MEMBACA KODE-KODE ILAHIAH PADA ORNAMEN MASJID - Zianda Alfarizzaki, Muhammad (Yayasan An-Nur Meunara Baro, 2025)
This article explores the intersection between mathematics and arabesque art in mosque ornamentation as a visual expression of the Islamic principle of tawhid. Employing a qualitative approach, the study combines visual and textual analyses of geometric patterns in classical mosques with philological examinations of Islamic scientific manuscripts. The findings reveal that arabesque art embodies complex mathematical structures such as fractal symmetry, the golden ratio, and tessellations, reflecting cosmic order and divine unity. Symbolic numbers like 5, 7, and 99 serve not only aesthetic purposes but also spiritual pedagogy. This art is not merely decorative but rich in cosmological and theological meaning. Classical Islamic artists integrated mathematical logic with Sufi spirituality to create transcendent visual forms. The symbolism of shapes such as circles and stars signifies the connection between the empirical world and metaphysical reality. Thus, arabesque should be interpreted as a visual revelation uniting science, art, and faith. The study suggests the importance of interdisciplinary approaches in Islamic art studies and highlights the potential for integrating geometric aesthetics into educational curricula rooted in Islamic values. Islamic visual heritage is more than a cultural legacy it reflects an epistemology in which true beauty lies in divine order.